2021
DOI: 10.1177/1756287221997186
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer biomarkers and multiparametric MRI: is there a role for both in prostate cancer management?

Abstract: Several advancements have been made in recent years with regards to the detection and evaluation of prostate cancer (PCa). The low specificity of prostate specific antigen (PSA) has left much to be desired in a test, but a boom in novel biomarkers has made screening and surveillance more complicated. Several attempts at identifying a niche for these tests has helped somewhat, but much is still undetermined about the benefit that each test provides. In addition to laboratory tests, advancements in multiparametr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 66 publications
0
13
0
2
Order By: Relevance
“…ConfirmMDx ® is a tissue-based gene assay that screens for epigenetic modifications identified in a prostate tissue sample. Alterations in DNA methylation in tumor suppressor genes (GSTP1, GASSF1, and APC) are identified by this assay, with the aim to stratify the risk of men with prior negative biopsies [ 153 , 154 ]. An original research by Artenstein et al [ 149 ], using mpMRI PIRADS score lesions after ConfirmMDx ® sampling, indicates that a negative ConfirmMDx ® test was somehow in accordance with negative MRI results (71.4%).…”
Section: Resultsmentioning
confidence: 99%
“…ConfirmMDx ® is a tissue-based gene assay that screens for epigenetic modifications identified in a prostate tissue sample. Alterations in DNA methylation in tumor suppressor genes (GSTP1, GASSF1, and APC) are identified by this assay, with the aim to stratify the risk of men with prior negative biopsies [ 153 , 154 ]. An original research by Artenstein et al [ 149 ], using mpMRI PIRADS score lesions after ConfirmMDx ® sampling, indicates that a negative ConfirmMDx ® test was somehow in accordance with negative MRI results (71.4%).…”
Section: Resultsmentioning
confidence: 99%
“…Multiparametric magnetic resonance imaging (mpMRI) with or without targeted biopsy has a well-established role in the detection of clinically significant PCa (csPCa) and an appealing alternative to transrectal ultrasonography (TRUS) biopsy [34][35][36] that was employed in this current study. Compared with systematic transrectal ultrasonographyguided biopsy, mpMRI is associated with a 57.0% improvement in the detection of clinically significant PCa and a 77% reduction in the number of cores taken per procedure [35,37]. Alkasab et al in evaluating the performance of PCA3 and MpMRI also reported an NPV of 40% and 83%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Prostate cancer (PCa) is traditionally diagnosed via digital rectal inspection (DRE) and a prostate-specific antigen (PSA) test, followed by transrectal ultrasound (TRUS)-guided biopsy [ 1 ]. Multiparametric MRI (mp-MRI) has recently been introduced as a standard part of the prostate cancer clinical diagnosis pathway [ 2 ]—it consists of T1- and T2-weighted images, diffusion-weighted (DW) images and dynamic contrast-enhanced (DCE) imaging. This technique has high sensitivity (90%) but moderate specificity (50%), translating to a high rate of false positive cases [ 3 ].…”
Section: Introductionmentioning
confidence: 99%